Проблемы минимизации рисков при аутсорсинге информационных услуг - Высоцкий, В. В. (НТУ "ХПИ", 2010)
Рассмотрены причины, приводящие к передаче управления информационными процессами и функциями на обслуживание другой организации (аутсорсинг), а также угрозы, возникающие при этом. Предложены технические и административные методы и способы уменьшения рисков, связанных с различными видами угроз информационной безопасности, возникающие при аутсорсинге ИТ-услуг.

The reasons leading to the transfer of information management processes and functions in the service of another organization (outsourcing), as well as the threats arising in this case. The technical and administrative methods and ways to mitigate the risks associated with various types of information security threats arising from the outsourcing of IT services.
Problems of minimization of risks at autsorsinge of informative services
Keywords: информационные процессы; ИТ-аутсорсинг; угрозы информационной безопасности; уменьшение рисков; information processes; soutsourcing; information security threats; reducing risks